Analisis Aspek Hukum Perjanjian Waralaba (Franchise) Dalam Perspektif Hukum Perdata - Moh. Adam sugiono; Sayyidah Dewi Hasanah; Sumriyah (JOURNAL SAINS STUDENT RESEARCH, 2023)
Currently, franchise business schemes are being widely used in society. Franchising, as a form of business investment, requires clear regulations to protect the rights and obligations of the parties involved. The main aim of this research is to provide a more comprehensive view of the legal implications in the franchise business model. The method used is normative juridical. The results of this research found that the importance of understanding Article 1320 of the Civil Code is fundamental in upholding the validity of franchise agreements, where conformity with the law is the main basis. Regulations such as PP Number 42 of 2007 and Minister of Trade Regulation Number 12/M-Dag/Per/3/2006 provide more detailed guidance regarding procedures, rights, obligations and procedures for registering franchise businesses.